Therapeutic Exercise in the Treatment of Primary Dysmenorrhea: A Systematic Review and Meta-Analysis. - Carroquino-García, Paloma; Jiménez-Rejano, José-Jesús; Medrano-Sanchez, Esther; De La Casa-Almeida, María; Díaz-Mohedo, Esther; Suárez-Serrano, Carmen (Oxford Academic, 2019)
Dysmenorrhea is a prevalent health issue with a significant societal and individual impact. While pharmacological treatments have proven effective, therapeutic exercise emerges as a low-cost, non-pharmacological alternative with no side effects. This systematic review aimed to assess the effectiveness of physical exercise in reducing pain intensity in women with primary dysmenorrhea, as well as its impact on pain duration and quality of life. A literature search was conducted from February to May 2017 across databases including Web of Science, PEDro, PubMed, Scopus, CINAHL, and Dialnet. Keywords included dysmenorrhea, exercise therapy, physical therapy, prevention, and pain. Randomized controlled trials involving women aged 16–25 with primary dysmenorrhea were included. Eligible studies applied exercise as treatment, measured pain intensity and/or duration, and evaluated quality of life. Exclusion criteria were gynecological disease, irregular cycles, surgery history, serious illness, or hormonal contraceptive use. From 455 initial records, 16 studies were selected for systematic review and 11 for meta-analysis. Two reviewers independently screened, extracted data, and assessed methodological quality using the PEDro scale. The review found moderate evidence supporting therapeutic exercise as effective in reducing pain intensity. Evidence was lower for reducing pain duration and improving quality of life. Meta-analyses confirmed significant positive outcomes in favor of exercise for both intensity and duration of pain. Limitations included intervention heterogeneity and risk of bias in some studies. In conclusion, therapeutic exercise is a useful tool for managing primary dysmenorrhea by decreasing pain intensity.
https://openpolicyfinder.jisc.ac.uk/id/publication/14964
Keywords: Dismenorrea - Tratamiento; Ciclo menstrual - Ejercicios terapéuticos; Dysmenorrhea; Physical exercise